Development and study of the operation made of a programmed current source for scanning electromagnet of technological electron linacs - Boriskin, V.N.; Reprintsev, L.V.; Tatanov, V.I.; Tsebenko, G.M. (Вопросы атомной науки и техники, 1999)
The investigation of the programmed current source for the beam scanning system has shown the possibility of flexible regulation of characteristics of electron beams at a linac exit.